Melampaui Tradisi: Evaluasi Dampak Kebijakan Politik Terhadap Pembaharuan Hukum Keluarga - Nurhuda, Rohmad (Institut Agama Islam Negeri Ponorogo, 2024)
Rapid changes in social and political dynamics have triggered a response from the government in the form of political policies aimed at creating family law that is more inclusive, fair and in line with the demands of the times. In line with the evolution of political policies affecting family law, there are essential questions that guide this research. First, how have political policies influenced reforms in family law? Second, to what extent have these changes been effective in achieving the goals of equality, justice and family welfare? Third, what are the challenges and obstacles that arise in the implementation of political policies related to family law reform? The policy analysis method, case study, and qualitative approach in this research are expected to provide a comprehensive picture of the complexity of the interaction between political policy and family law reform, as well as its impact on society. The development of family law in Indonesia reflects a journey from conservative norms towards increased individual rights, gender equality and family diversity. The results of this study show that the implementation of political policies related to family law reform faces a number of challenges, including resistance from conservative groups and skepticism among the Muslim community. Ambiguity in the criteria for change, changing political dynamics, and controversy surrounding the practice of underage marriage are obstacles to achieving consistency and clarity in implementation. In addition, the need for balance between positive and Islamic law emphasizes the importance of dialogue and cooperation across sectors to achieve an effective and sustainable vision of family law reform. With this balance in mind, this study emphasizes that constructive and inclusive dialogue between the government, the Muslim community, and other stakeholders is key to ensuring that changes to family law are acceptable to all parties and remain consistent with constitutional values and respected sharia principles.